Impact of Anemia on Preterm Labor in Hypothyroid Patients: A Retrospective Study [31N]. (May 2017) - Araji, Sarah; Khoury, Aldo; Elkafrawi, Deena; Miller, Jacob; Ching, Michael
Abstract : INTRODUCTION: Studies have demonstrated that hypothyroidism in pregnancy is associated with an increased risk of preterm delivery. Current literature fails to demonstrate whether the underlying cause is thyroid dysfunction or anemia of thyroid disease. A negative association between anemia and duration of gestation was reported in the majority of studies; however, the exact mechanism of action is not determined. In this retrospective study, we evaluate anemia as a risk factor for preterm labor in pregnant patients with hypothyroidism. METHODS: A retrospective chart review of patients delivered before 37 weeks and received prenatal care at our outpatient clinic between January 2013-August 2015 was conducted. TSH, T4, and H/H levels during the course of pregnancy and before delivery was evaluated. We indicated if patients received levothyroxine or iron supplements. RESULTS: Our sample size was 373 pregnant women who delivered before 37 weeks--202 of 373 were neither anemic nor hypothyroid (54.2%), 124 of 373 were anemic only (33.2%), 25 of 373 were hypothyroid and anemic (6.70%), and 23 of 373 were hypothyroid only (6.17%). Anemia had no impact on gestational age when stratified by hypothyroidism. Increasing T4 increased risk of preterm delivery starting from 35.6 weeks of gestation (P=0.00; 95% CI, -1.40 to -0.57) regardless of anemic status. CONCLUSION: Anemia does not play a significant role in causing preterm delivery in hypothyroid pregnant patients. T4 was directly proportional to preterm delivery in anemic and non-anemic patients. Age was inversely proportional to preterm delivery in anemic and non-anemic patients alike.